Family abuse of the elderly; a case study in nuevo león, mexico (2002)
The ongoing demographic transition in developing countries and particularly in Mexico has turned family care of the elderly into a subject of increasing importance. This study documents and examines an experience of elderly abuse and the conduct of the victim towards it, in a municipality to the south of the state of Nuevo León, Mexico, 2001. Qualitative information was obtained through open interviews and in situ observations in the place where both the victim and its aggressors interact. From the descriptive analysis diverse forms and manifestations of abuse are highlighted as well as the victim ´s responses as regards to seeking help. The analysis of this case is also carried out bearing in mind the theories of social psychology on elderly abuse. The complex victimization poses a challenge both for research and for policy-making on how to handle family abuse in this vulnerable agegroup.